Aging Effects on the Neuroplastic Attributes of Multisensory Cortical Networks as Triggered by a Computerized Music Reading Training Intervention. (14th August 2020) - Paraskevopoulos, Evangelos; Chalas, Nikolas; Karagiorgis, Alexandros; Karagianni, Maria; Styliadis, Charis; Papadelis, Georgios; Bamidis, Panagiotis
Abstract: The constant increase in the graying population is the result of a great expansion of life expectancy. A smaller expansion of healthy cognitive and brain functioning diminishes the gains achieved by longevity. Music training, as a special case of multisensory learning, may induce restorative neuroplasticity in older ages. The current study aimed to explore aging effects on the cortical network supporting multisensory cognition and to define aging effects on the network's neuroplastic attributes. A computer-based music reading protocol was developed and evaluated via electroencephalography measurements pre- and post-training on young and older adults. Results revealed that multisensory integration is performed via diverse strategies in the two groups: Older adults employ higher-order supramodal areas to a greater extent than lower level perceptual regions, in contrast to younger adults, indicating an age-related shift in the weight of each processing strategy. Restorative neuroplasticity was revealed in the left inferior frontal gyrus and right medial temporal gyrus, as a result of the training, while task-related reorganization of cortical connectivity was obstructed in the group of older adults, probably due to systemic maturation mechanisms. On the contrary, younger adults significantly increased functional connectivity among the regions supporting multisensory integration.